Peran Kepemimpinan Transformasional dalam Meningkatkan Kinerja Individu Santri pada Unit Usaha Pondok Pesantren - Fuad Dhiya Ul Husaen; Reni Rosari (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to determine how much influence transformational leadership on the individual performances of santri, mediated by the innovative behavior of santri. This research is confirmatory research that aims to examine theories that have been there before. The number of samples in this study was 102 students who worked in the business unit of the Sidogiri Islamic boarding school. The sample selection uses a purposive sampling technique. Data was collected using a questionnaire instrument with a Likert scale. Testing the hypothesis refers to Baron Kenny's mediation theory and processing data using Smart PLS 3 applications, by analyzing the results of evaluating the outer and inner models. The results of this study indicate that; (1) transformational leadership of the head of a business unit has a significant positive effect on the individual performance of students with a coefficient of 0.546. (2) innovative behavior proved not to mediate the influence of transformational leadership head of the unit on individual student performance.